Diabetic retinopathy management by Australian optometrists - Ting, D.; Ng, Jonathon; Morlet, Nigel; Yuen, J.; Clark, A.; Taylor, H.; Keeffe, J.; Preen, D. (2011)
Background: To survey the current diabetic retinopathy screening and management practices of Australian optometrists following the release of the 1997 National Health Medical Research Council Diabetic Retinopathy Management Guidelines. Design: Cross-sectional national survey, primary care setting. Participants: 1000 Australian optometrists across different states. Methods: A self-administered questionnaire was sent to 1000 optometrists across all states during 2007/2008. Main outcome measures: Use of retinal camera, screening practices/attitudes and behaviour in diabetic retinopathy management. Results: 568 optometrists (57%) responded to the survey. Patients' unpreparedness to drive post dilation (51%) and the fear of angle closure glaucoma (13%) were the two main barriers to optometrists not performing dilated ophthalmoscopy. Those who had strong desire to screen for diabetic retinopathy were more likely to use a retinal camera (p < 0.005). Use of a retinal camera was significantly associated with an increased confidence in detecting clinical signs of diabetic retinopathy including macular oedema (P < 0.001). Optometrists who read the guidelines at least once were 2.5-times (P < 0.001)) more likely to have confidence in detecting macular oedema than those who had never read the guidelines. Although they may be confident in diagnosis, and may use retinal cameras for screening, nearly 60% of optometrists would not refer patients with macular oedema to an ophthalmologist. Conclusions: Despite their self-reported desire for involvement in diabetic retinopathy, the management of macular oedema by Australian optometrists needs improvement. The use of retinal cameras and promotion of the 2008 NHMRC guidelines should be encouraged to improve overall optometric diabetic retinopathy management, particularly with macular oedema.